2017
DOI: 10.1186/s40794-017-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting prevention and control of malaria among endemic areas of Gurage zone: an implication for malaria elimination in South Ethiopia, 2017

Abstract: BackgroundGlobally malaria remains one of the most severe public health problems resulting in massive morbidity particularly in developing countries. Ethiopia as one of the sub-Saharan country it is highly endemic to malaria. It was noted that early detection and prompt treatment of malaria cases, selective vector control and epidemic prevention and control are the major strategies for malaria prevention and control; So far, a lot have been done and remarkable improvements were seen. However, in what extent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 5 publications
1
27
2
Order By: Relevance
“…This study found that more families from the middle (61.8%) and upper (34.8%) social class practiced the use of ITNs. This is in tandem with another study where ITNs use rate had a positive correlation with educational status of the study participants [25]. Despite the fact that ITNs are often given out free or at minimal cost, its ownership and use was mainly by the middle and upper class.…”
Section: Resultssupporting
confidence: 80%
“…This study found that more families from the middle (61.8%) and upper (34.8%) social class practiced the use of ITNs. This is in tandem with another study where ITNs use rate had a positive correlation with educational status of the study participants [25]. Despite the fact that ITNs are often given out free or at minimal cost, its ownership and use was mainly by the middle and upper class.…”
Section: Resultssupporting
confidence: 80%
“…This variation might be due to climatic and altitude differences. In the previous study, endemic areas of Gurage zone had a good practice of malaria prevention measures accounted for 62% [20]. Moreover, according to 2018 Gurage zone health bureau report, the overall coverage of main malaria interventions, ITNs and IRS, has reached 88% in Gurage zone where Wolkite town accounted 95.6%, Abshge 87%, Kebena 95.5% which attributed for the reduction of malaria incidence [11].…”
Section: Discussionmentioning
confidence: 99%
“…(9,13,16,17) similarly, environmental managements like breeding site reduction and clearing was mentioned by 76.1% of respondents as malaria prevention method which is higher than studies done in Arba Minch and Gurage. (18,19) Despite this closing windows and doors at an early time in the evening and using aerosol is mentioned at a lower rate. Only 3.7% and 2.3% of the respondents mentioned these as malaria prevention methods respectively.…”
Section: Discussionmentioning
confidence: 99%